SIMULASI PERAMBATAN RETAK LELAH PADA POROS AISI 1045 YANG DIKENAI BEBAN DINAMIK LENTUR AMPLITUDO TEGANGAN KONSTAN - Akhyar Akhyar; Ahmad Taufik Joenoes; Syoni Suprijanto (Mesin, 2002)
The current research was carried out to study the change of stress intensity factor (KI) on the semielliptical cracked crank subject to a constant amplitude cyclic loading. This research was also carried out to find the fatigue crack propagation model, the critical crack depth and to predict the fatigue life. The study was performed by using computer modeling and simulation, verified by series of fatigue tests on 15 mm diameter rod specimens made of AISI 1045 steel. The crack (0.5 mm) was introduced on the specimen surfaces as a crack initiation site. The result shows that, for the same crack depth, the higher the loading magnitude, the higher the stress intensity factor, and also, at the end of the crack propagation, semi-elliptical crack tends to be semi-circular one, or a/c ratio approaching unity (1.0). The fatigue experiment has been successfully verified that the critical crack depth and the fatigue life lie within 89% to 92% accuracy, and 8% to 10% deviation , respectively, compared to those obtained by the computer simulation. Fractography study has also revealed that the fracture path consist of; i) crack initiation site, ii) crack propagation, as indicated by beach mark, and iii) the final fracture.